2016
DOI: 10.3389/fpsyg.2016.00898
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Enjoyment and Self-Efficacy As Predictors of Cancer Patients' Physical Activity Level

Abstract: Background: Physical activity (PA) can support cancer patients during medical treatment by reducing side-effects and increasing quality of life. However, PA levels mostly decline after diagnosis. Which factors can explain if patients are able to remain or even increase their PA level? Self-efficacy is an important cognitive factor that has been linked to cancer patients' PA across many studies. In contrast, affective factors such as PA enjoyment have rarely been examined. We compare the influence of self-effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 61 publications
4
39
1
1
Order By: Relevance
“…Third, patients were allowed, within certain limits, to choose their own activities. Current evidence suggests that exercise enjoyment is an important determinant of physical activity and exercise self-efficacy [28, 29]. These elements are aimed at implementation of regular exercise in patients’ daily routines and may aid continuing to exercise after the intervention period had ended [27, 30].…”
Section: Discussionmentioning
confidence: 99%
“…Third, patients were allowed, within certain limits, to choose their own activities. Current evidence suggests that exercise enjoyment is an important determinant of physical activity and exercise self-efficacy [28, 29]. These elements are aimed at implementation of regular exercise in patients’ daily routines and may aid continuing to exercise after the intervention period had ended [27, 30].…”
Section: Discussionmentioning
confidence: 99%
“…Cancer patients face further obstacles on account of their condition (e.g., cancer-related fatigue, muscle weakness, nausea, sleep disorders) [22,23]. To develop a successful exercise intervention, cancer patients' barriers and preferences must be considered, allowing them to pick the activities they perceive as beneficial and enjoyable [23][24][25][26]. International studies investigated the preferences and determinants of exercise levels in cancer patients and survivors [18,[27][28][29][30][31][32][33], but data on the Italian population are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Husebo and colleagues found in a systematic review and metaanaly sis that the TTM and the planned behaviour were significantly associated with better exercise adherence [35]. Some studies have found that 2 important factors to increase the physical activity are self-efficacy and enjoyment [36] but also that individual supervising by a therapist during rehabilitation is necessary [35,37]. In our study, patients benefited from the combined modules aftercare-planning and telephone-support but also from the module aftercare-planning alone which may infirm this later statement.…”
Section: Discussionmentioning
confidence: 99%